Dextrocardia, Situs Ambiguos and Totalis Inversus: Nursing scholars in the childcare consultation - report of experience in Primary Care (Research, Society and Development, 2021)
Objective: to describe how Supervised Internship I can contribute to the performance of nurses in relation to children with dextrocardia. Methodology: this is an experience report of a descriptive-exploratory characteristic and a qualitative approach carried out in 2019. Results: As it is an unusual pathology, nurses come to understand it better during childcare consultations, a time when they should exercise the role of educator towards parents. The performance of this professional is based on the use of Nursing Care Systematization to diagnose his main needs. However, due to the rarity of the disease, there is a limitation in relation to the care of nurses in relation to children with congenital heart disease. Final Considerations: the importance of monitoring the nurse in childcare consultations is highlighted, since this care is not restricted only to the pathology itself, but also to the general care provided to them.